2015
DOI: 10.3168/jds.2014-8586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus acidophilus NS1 on plasma cholesterol levels in diet-induced obese mice

Abstract: We investigated the probiotic properties of Lactobacillus acidophilus NS1, such as acid resistance, bile tolerance, adherence to HT-29 cells, and cholesterol assimilation activity. In an animal study, 7-wk-old male C57BL/6 mice were fed a normal diet, a high-fat diet (HFD), or an HFD with L. acidophilus NS1 (ca. 1.0×10(8) cfu/mL) for 10 wk. Total cholesterol and low-density lipoprotein (LDL) cholesterol levels were significantly lower in mice fed an HFD with L. acidophilus NS1 than in those fed an HFD only, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 29 publications
(34 reference statements)
6
38
1
3
Order By: Relevance
“…Likewise, it was not possible to assess the impact of other potential probiotic cholesterol-lowering mechanisms such as the conversion of cholesterol to coprostanol, short chain fatty acid production 55 and the assimilation of bile acids 56, 57 . Probiotics have also been shown to reduce blood TG levels 37, 38 or impart anti-inflammatory effects 34, 40 in HFD fed C57BL/6J mice but these responses were not seen in our study (Table 1) possibly as a result of the short intervention period.…”
Section: Discussioncontrasting
confidence: 67%
“…Likewise, it was not possible to assess the impact of other potential probiotic cholesterol-lowering mechanisms such as the conversion of cholesterol to coprostanol, short chain fatty acid production 55 and the assimilation of bile acids 56, 57 . Probiotics have also been shown to reduce blood TG levels 37, 38 or impart anti-inflammatory effects 34, 40 in HFD fed C57BL/6J mice but these responses were not seen in our study (Table 1) possibly as a result of the short intervention period.…”
Section: Discussioncontrasting
confidence: 67%
“…Lactobacillus acidophilus 45 , Lactobacillus gasseri 46 , Lactobacillus curvatus and Lactobacillus plantarum 47 have all been successfully used as effective disease modifiers for obesity, we tentatively put forward that fucoidan may have gut microbiota as its primary drug target during the treatment of obesity. Interestingly, a recent study partly echoed our hypothesis by demonstrating that fucoidan from Fucus evanescens (FuF) can enrich the biomass of B. longum and B. bifidum both in vivo and in vitro 18 .…”
Section: Key Phylotypes Of Gut Microbiota Modulated By Ful and Fua Trmentioning
confidence: 96%
“…Active uptake of bacteria can lead to a decrease in serum cholesterol levels by inhibiting the enterohepatic circulation of bile salts and providing deconjugation of bile salts. Therefore, free bile acids are less soluble than the conjugated bile salts and are less absorbed from the intestinal tract (Corzo and Gilliland ; Pereira et al ; Song et al ). Rossi et al () found that cholesterol‐lowering abilities of E. faecium and different lactic acid bacteria varied depending on the species, and some cultures lowered the cholesterol at higher rates.…”
Section: Resultsmentioning
confidence: 99%